Use of plasma oxidation for conversion of metal salt infiltrated thin polymer films to metal oxide. (3rd November 2022) - Conway, J; Snelgrove, M; Yadav, P; Shiel, K; Lundy, R; Selkirk, A; O'Connor, R; Morris, M A; Turner, M M; Daniels, S
Abstract: Oxygen plasma treatments for conversion of metal salt infiltrated polymer films to metal oxide films using an asymmetrical capacitively coupled plasma system were investigated. Hydroxylated Poly-2-Vinylpyridine (P2VP-OH) thin films grafted to silicon were exposed to metal salt-solvent solutions which swell the polymer enabling metal ion infiltration. Exposing the resulting film to oxygen plasma resulted in formation of polymer-free metal oxide films. Atomic oxygen and positive ions present in plasma can both influence the process outcome. A design of experiment approach was used to investigate the impact of radio frequency (RF) power, gas pressure and process time on plasma composition and the resulting metal oxide films. A combination of Langmuir probe, retarding field energy analyser and optical emission spectroscopy measurements were used to monitor the plasma. The samples surfaces were examined using x-ray photoelectron spectroscopy, ellipsometry, transmission electron microscopy and energy dispersive x-ray analysis. Gas pressure and RF power were found to strongly influence both ion energy, and atomic oxygen to molecular ion ratios [O]/[O2 + ] in the plasma which impacted the resulting surface layer. For the plasma conditions investigated conversion to a metal oxide was achieved in minutes. Sputter contamination was found to be significant in some cases.